2016
DOI: 10.1021/acs.biochem.6b00727
|View full text |Cite
|
Sign up to set email alerts
|

The Influenza M2 Ectodomain Regulates the Conformational Equilibria of the Transmembrane Proton Channel: Insights from Solid-State Nuclear Magnetic Resonance

Abstract: The influenza M2 protein is the target of the amantadine family of antiviral drugs, and its transmembrane (TM) domain structure and dynamics have been extensively studied. However, little is known about the structure of the highly conserved N-terminal ectodomain, which contains epitopes targeted by influenza vaccines. In this study, we synthesized an M2 construct containing the N-terminal ectodomain and the TM domain, to understand the site-specific conformation and dynamics of the ectodomain and to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…These studies suggest that the ED conformation depends on the membrane composition. In DMPC bilayers, some residues show a β-strand conformation that shifts to an α-helical conformation in the presence of cholesterol (mimicking the viral membrane) [ 74 , 75 ]. It is worthwhile to mention that crystallography of M2 ED—Fab complex also suggested that M2-ED exists in different conformations supporting the notion that M2-ED is intrinsically disordered [ 76 , 77 ].…”
Section: Structure and Function Of The M2 Ion Channelmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies suggest that the ED conformation depends on the membrane composition. In DMPC bilayers, some residues show a β-strand conformation that shifts to an α-helical conformation in the presence of cholesterol (mimicking the viral membrane) [ 74 , 75 ]. It is worthwhile to mention that crystallography of M2 ED—Fab complex also suggested that M2-ED exists in different conformations supporting the notion that M2-ED is intrinsically disordered [ 76 , 77 ].…”
Section: Structure and Function Of The M2 Ion Channelmentioning
confidence: 99%
“…The post-APH CT up to residue 71 is largely unstructured with random coil conformation, highly mobile and, unlike the ED, insensitive to the membrane composition [ 75 , 78 ]. Together, these studies suggest that the presence of either the ED or CT favors TMD conformation towards a more stable, resembling drug bound state [ 74 , 75 , 78 ]. Moreover, the post-APH CT also changes the TMD conformation to one favoring proton binding, though its deletion does not affect the ion channel activity [ 74 ].…”
Section: Structure and Function Of The M2 Ion Channelmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies showed that the conduction-relevant structure of M2 depends markedly on the membrane environment [18], but the conduction properties are insensitive to the construct length beyond the TM domain if the same membrane environment is used [19]. Several M2 constructs have been used in biophysical studies because of the modular sequence and multifunctional nature of this protein: a highly conserved and disordered N-terminal ectodomain [20] mediates protein incorporation into the virion [21] and is the target of universal influenza vaccines [22]. The TM domain (residues 22-46) is necessary and sufficient to exhibit proton conductance that is similar to full-length M2 [19].…”
Section: Introductionmentioning
confidence: 99%
“…The AM2 channel is a homotetrameric transmembrane protein with 97 residues per monomer. The N-terminal domain (residues 1-23) is largely unstructured with polar residues that help increase the hydration of the pore to facilitate proton conductance (Kwon and Hong, 2016;Ma and Wang, 2018) and for incorporation into virions (Park et al, 1998). The transmembrane (TM) domain (residues 24-43) is required for the formation of a left-handed 4-helix bundle (Cady and Hong, 2008;Stouffer et al, 2008) and for both proton conductance and selectivity (Balannik et al, 2010) as well as drug binding (Ma et al, 2009).…”
Section: Introductionmentioning
confidence: 99%